Order-unit-metric spaces - Çağlar, Mert; Ercan, Zafer (Springer, Van Godewijckstraat 30, 3311 Gz Dordrecht, Netherlands, 2014)
We study the concept of cone metric space in the context of ordered vector spaces by setting up a general and natural framework for it.
Keywords: Cone metric space; Ordered vector space; Order unit; Interior of cone; Metrizability; Fixed-Point Theorems; Contractive Mappings